Murine Abdominal Aortic Aneurysm Intraluminal Thrombus Composition and Structure - Cortland H. Johns; Luke E. Schepers; Annabelle M. F. Foist; Ethan P. Foster; Anish Bedi; Niharika Narra; Claudia K. Albrecht; Abigail D. Cox; Craig J. Goergen (Annals of Biomedical Engineering, 2026)
Purpose Many abdominal aortic aneurysm (AAA) patients develop intraluminal thrombus (ILT), but the role of ILT in AAA progression and rupture is poorly understood. Methods To evaluate ILT in AAAs, we induced AAAs in C57Bl6/J mice via surgical application of topical elastase to the abdominal aorta below the renal arteries and administration of β-aminopropionitrile (BAPN) in drinking water. Ultrasound images of these AAAs were collected longitudinally over a period of 56 days to evaluate AAA growth over time. We semi-quantitatively assessed elastin degradation and inflammation from Movat’s pentachrome and H&E-stained samples, respectively. Additionally, we assessed extracellular matrix composition and elastin quality through Movat’s pentachrome stained samples. Results Mice subjected to elastase + BAPN exhibited continuous and significant AAA growth over time. Mice with ILT had more significant expansion over the length of the study ( p Conclusion Understanding the relationship between ILT formation, aortic wall degradation, and inflammation could help refine clinical strategies for monitoring and treating AAAs. These data suggest that work focused on modulating inflammation and ILT formation could offer promising pathways for non-surgical intervention in AAA treatment.